Effect of mushroom powder supplementation on the growth performance and carcass yield of broiler chicken (Agriculture, Food, and Natural Resources Journal, 2026)
The study was conducted to investigate the effect of varying inclusion levels of mushroom (Pleurotus ostreatus) meal on the growth performance and carcass characteristics of broiler chicken. One-hundred-and-twenty-Ross 308-day-old broiler chicks were randomly assigned to 4 dietary treatments with 30 birds per treatment. A treatment had 3 replicates with 10 birds per replicate. Mushroom powder (MP) was included at varying levels (0, 1, 1.5, 2%) in the formulated starter and finisher diets fed to the birds for 8 weeks, the duration of the experiment.  Feed intake, body weight, carcass characteristics (thigh, wing, drumstick, shank, head, neck, gizzard, liver, heart, defeathered weight, carcass weight, and dressing %) were monitored during and at the end of the study, The data collected were subjected to analysis of variance. Treatment means were compared at a 5% probability level using Fisher's least Significant difference. Proximate analysis showed that the crude protein, fibre, ether extract, and metabolizable energy are within the nutritional requirements of the studied birds, indicating that it is a highly nutritious feed ingredient. The total feed intake was significantly (P < 0.05) influenced by the dietary treatment with broilers fed at a 2% inclusion level of MP recording the highest value compared to the other treatment groups. Dietary treatment had no significant effect on the weight gain of the birds. Supplementing with mushroom powder significantly influenced the carcass yield and organ weight of broiler chicken, with the highest values (P